The relationship between rewards system and job performance among support staffs at Sekolah Menengah Pendidikan Khas Vokasional Indahpura / Nur Adibah Abd Razak - Abd Razak, Nur Adibah (2018)
Employees’ motivations can leads to the successful of the organization. Rewards are one of the mechanisms that can be used to attract employees’ motivation. Researcher used Herzberg’s Motivation-Hygiene Theory by Herzberg (1968) for this study. Based on this theory, the researcher trying to discover is there any relationship between extrinsic (working condition, salary, performance bonuses) or intrinsic rewards (recognition, promotion) with job performance. Therefore, this research aimed to investigate the relationship between extrinsic and intrinsic rewards with the job performance. By using quantitative approach, one hundred questionnaires were distributed to the subjects of this research that are the support staffs at Sekolah Menengah Pendidikan Khas Vokasional Indahpura. The data was analyzed through Statistical Packages for the Social Science (SPSS). The analysis showed that the data is considered normal and no missing data identified. 5-point likert scale was used to measure the level of agreement. The data considered reliable and have moderate significant and positive relationship on the average for correlation test. The result from this research proves that there is a relationship between extrinsic and intrinsic rewards with the job performance. Both of extrinsic and intrinsic rewards are important to increase employee job performance. Researcher recommend that the future research can investigate on what type of research that have more impact on the support staffs and top management staff so that the organization can provides better rewards to motivate their employee based on what they need the most within the organization budget.